Efficacy of newer insecticides against Spodoptera litura in groundnut (Arachis hypogaea L.): EFFICACY OF NEWER INSECTICIDES AGAINST SPODOPTERA LITURA IN GROUNDNUT - M VENKATAIAH; B ANIL KUMAR; SREEDHAR CHAUHAN (Journal of Oilseeds Research, 2015)
Field experiments were conducted during rabi/summer season of 2010-11 and 2011-12 to evaluate the efficacy of five newer insecticides (chlorantraniliprole, flubendiamide, spinosad, thiodicarb, novaluron) with two conventional insecticides (dichlorvos and chlorpyriphos) against tobacco caterpillar, Spodoptera litura in groundnut. The experiments were conducted in a randomized block design with eight treatments and three replications. The results revealed that the maximum percentage of larval reduction and defoliation was in flubendiamide 480SC @ 150 ml/ha followed by chlorantraniliprole 20SC @ 125 ml/ha and novaluron 10EC @ 500 ml/ha. Highest dry pod yield of groundnut was recorded in flubendiamide (2650 and 2100 kg/ha) followed by chlorantraniliprole (2500 and 1983 kg/ha) and novaluron (2267 and 1958 kg/ha) as against 1750 and 1375 kg/ha in untreated control during 2010-11 and 2011-12, respectively. The maximum cost-benefit ratio of 1: 2.5 and 1: 2.13 was obtained with flubendiamide during 2010-11 and 2011-12, respectively.